Biomass Gasifier Energy Cyber-Physical System Design with Coupling of the Wind and Solar Energy - Zhihuan Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The air pollution in China has been quite serious, and biomass is extremely rich in large agricultural country. In the view of current situation, highly efficient solar collectors, wind energy and solar energy coupled heating straw gasification system is studied. The stability of continuous gas production is analyzed in various weather conditions including windy, calm, sunny and cloudy. Highly efficient solar panels, wind energy and solar energy coupled heating straw gasification control system is raised. This system overcomes the time variability of the weather conditions to ensure the stability of the continuous gas production under a variety of weather conditions. It has high quality of gas production, strong anti-interference ability and robustness. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3750